ANALISIS PENGARUH FINANCIAL ATTITUDE,FINANCIAL BEHAVIOR, DAN FINANCIAL KNOWLEDGE TERHADAP TINGKAT LITERASI KEUANGAN - Irma Agustiani; Sri Yani Kusumastuti (Triwikrama: Jurnal Ilmu Sosial, 2023)
This study aims to analyze and test the variable indicators of measuring financial literacy through three measurement indicators, namely Financial Attitude, Financial Behavior and Financial Knowledge on increasing levels of financial literacy. This study uses a quantitative method with non probability sampling technique. the population in this study is a community that is limited to at least 17 yearswith a minimum education level of high school (Equivalent) and feels the influence of Financial Literacy, with sample data obtained as many as 250 respondents. the data is processed using the Structural Equation Model (SEM) technique using the SPSS 22 and Amos 24 analysis tools. The results of this study indicate that Financial Attitude has a significant effect on Financial Literacy, Financial Behavior has a significant effect on Financial Literacy and Financial Knowledge has a significant effect on Financial Literacy.